Correlation between UGT1A1 Polymorphism and Neonatal Hyperbilirubinemia of Neonates in Wuhan - 刘伟;常立文;谢敏;李文斌;容志惠;吴莉;陈玲 (Current medical science, 2017)
This study attempts to discuss the correlation between UGT1A1＊28 as uridine diphosphate glucuronosyltransferase gene promoter and coding region Gly71 Arg gene polymorphism with neonatal hyperbilirubinemia of neonates in Wuhan. A total of 168 neonates were divided into the hyperbilirubinemia group（case group, n=108） and healthy neonates group（control group, n=60）. Their DNA was obtained through blood extraction. The gene exon mutation of UGT1A1 was detected by Sanger sequencing, which revealed the relationship between UGT1A1＊28 and Gly71 Arg polymorphism with neonatal hyperbilirubinemia of neonates. The results showed that：（1） The frequency of UGT1A1＊28 allele mutation in the case group and the control group was 9.3% and 10% respectively, with the difference being not significant between the two groups（P〉0.05）.（2） The frequency of Gly71 Arg allele mutation in the case group and the control group was 35.1% and 21.7% respectively, with the difference being significant between the two groups（P〈0.01）.（3） The serum bilirubin level of Gly71 Arg mutant homozygous and heterozygous subgroups（n=66） in the case group was 302.7±31.4 μmol/L, which was significantly higher than 267.3±28.5 μmol/L of the wild subgroup（n=42）（P〈0.01）. It was suggested that the occurrence of neonatal hyperbilirubinemia of neonates in Wuhan was not associated with UGT1A1＊28 gene polymorphism, but closely with the Gly71 Arg gene polymorphism. Meanwhile, the Arg allele mutation was related to the degree of jaundice.